Challenges of rehabilitation in Colombia in the COVID-19 pandemic - Wilches-Luna, Esther Cecilia (2021)
The COVID-19 pandemic has left nearly 70.000 deaths in Colombia and presents great challenges to the health care system. Rehabilitation professionals play a fundamental role in the recovery of many people who have suffered COVID-19 and have had to adapt to the consequences caused by the pandemic, reorganizing the care protocol to be able to meet the rehabilitation needs during the acute, subacute, and long-term phases. In this context, it seeks to identify and reflect on the challenges of rehabilitation implicit in the management of people with COVID-19.